A versatile AIE fluorogen with selective reactivity to primary amines for monitoring amination, protein labeling, and mitochondrial staining. Issue 1 (7th June 2022) - He, Xinyuan; Xie, Huilin; Hu, Lianrui; Liu, Pengchao; Xu, Changhuo; He, Wei; Du, Wutong; Zhang, Siwei; Xing, Hao; Liu, Xinyue; Park, Hojeong; Cheung, Tsz Shing; et al.
Abstract: Specific bioconjugation for native primary amines is highly valuable for both chemistry and biomedical research. Despite all the efforts, scientists lack a proper strategy to achieve high selectivity for primary amines, not to mention the requirement of fast response in real applications. Herein, we report a chromone‐based aggregation‐induced emission (AIE) fluorogen called CMVMN as a self‐reporting bioconjugation reagent for selective primary amine identification, and its applications for monitoring bioprocesses of amination and protein labeling. CMVMN is AIE‐active and capable of solid‐state sensing. Thus, its electrospun films are manufactured for visualization of amine diffusion and leakage process. CMVMN also shows good biocompatibility and potential mitochondria‐staining ability, which provides new insight for organelle‐staining probe design. Combined with its facile synthesis and good reversibility, CMVMN would not only show wide potential applications in biology, but also offer new possibilities for molecular engineering. Abstract : A chromone‐based aggregation‐induced emission (AIE) fluorogen called CMVMN as a self‐reporting bioconjugation reagent for selective primary amine identification in situ was reported, along with its applications of monitoring bioprocesses of amination, protein labeling, and mitochondria staining. It is capable of solid‐state sensing and its electrospun films are manufactured for visualization of amine diffusion and leakage process.